2018
DOI: 10.5812/ircmj.56550
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting Transient Tachypnea of the Newborn in Fatemieh Hospital of Hamadan, Iran, 2015 - 2016

Abstract: Background: Transient tachypnea of the newborn (TTN) is one of the important causes of neonatal respiratory distress and hospitalization in the neonatal intensive care unit (NICU). Objectives: The current study aimed at identifying the risk factors of TTN in a single tertiary care center. Methods: The current prospective, case-control study was conducted on 180 newborns allocated in the 2 groups of with TTN (n = 90) as the case group, and without TTN (n = 90) as the control group for 1 year from April to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…The mortality rate of 27.2% observed in this study is higher than that reported by some authors, which ranges from 2% to 24.5% [7,8,[10][11][12]14,[18][19][20].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The mortality rate of 27.2% observed in this study is higher than that reported by some authors, which ranges from 2% to 24.5% [7,8,[10][11][12]14,[18][19][20].…”
Section: Discussioncontrasting
confidence: 67%
“…Barring unreported cases, the causes of NRD are well documented and classified [21,22]. Respiratory pathologies are the main causes of NRD, according to most authors [6,7,19,20], although their frequency may vary, respiratory causes are followed by perinatal asphyxia, sepsis, and congenital malformations.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher chance of seizures during the first month of life. 2,3 The four distinct clinical seizure types are myoclonic, clonic, tonic, and subtle. Each one can be widespread, multifocal, or focal.…”
Section: Original Article Original Articlementioning
confidence: 99%
“…1 Neonatal seizures are characterized by aberrant motor, autonomic, and behavioral activity and are characterized by paroxysmal brain dysfunction. 2 They pose a significant risk for eventual neurological impairment or death, and they can independently have a negative impact on a neonate's neurodevelopmental outcome. Because of subtle form of seizure is more common seizure during the neonatal period, it is highly challenging to identify.…”
Section: Introductionmentioning
confidence: 99%